89 GENE THERAPY: POTENT CYTOTOXIC T LYMPHOCYTE ACTIVITY BY ADENO-ASSOCIATED VIRUS/CORE-HEPATITIS C VIRUS GENE DELIVERY INTO DENDRITIC CELLS. (1st January 2006) - Chiriva-Internati, M.; Grizzi, F.; Frezza, E.; Cobos, E.
Abstract : Purpose: Many cases of chronic hepatitis C virus (HCV) infection are resistant to conventional therapies. Such cases might be treated by cell-mediated immunotherapy as cytotoxic T lymphocytes (CTL) are the main mechanism by which viral infections are cleared. The HCV core gene, being well conserved among HCV types, may be an appropriate antigen for targeting HCV-infected cells. Methods: Here a series of five recombinant adeno-associated virus (rAAV) vectors carrying the full length (aa1-190) or autoimmune domain-depleted (AIDD) versions of core were used to load dendritic cells (DC), which, in turn, stimulated anti-core CTL. The AAV vectors were found to be able to transduce 88 to 95% of DC and the transduced DC displayed higher levels of CD80, CD83, CD86, and CD1a over controls. One vector, AAV/core(49-180)/Neo, with both autoimmune domains deleted from core, stimulated comparable core-positive target killing to the other versions yet stimulated significantly lower levels of "self " killing of core negative-targets, either of autologous PBMC targets (p = .002) or HLA-matched HepG2 liver cancer cells (p = .001). Results: The resulting CTL populations displayed higher IFN-g expression, higher CD8:CD4 ratios, and lower CD56:CD8 ratios than controls. The rAAV loading-derived CD8+ T cells had more CD69+ cells and the CD4+ T populations had fewer CD25+ cells than controls. Summary and Conclusion: AAV/core(49-180)/Neo, containing a dual AIDD core gene, may be particularly useful for clinical treatments as it stimulates lower "self " recognition but stimulates robust anticore CTL activity.